Assessing knowledge and religiosity on consumer behavior towards halal food and cosmetic products - Ahmad, Ahlam Nuwairah; Abd Rahman, Azmawani; Ab Rahman, Suhaimi (International Association of Computer Science and Information Technology Press, 2015)
This paper investigates the relationship between knowledge and religiosity on attitude towards Halal food and cosmetic products. It also looks at existence of significant difference between consumers’ attitude towards Halal cosmetic and Halal food products were investigated. Based on the sample of Malaysian Muslim consumers, results show that religiosity is more influential towards behavior compared to knowledge pertaining to halal matters and there is a significant difference on respondent’s behavior between halal food products and halal cosmetic products. The results of the study give implication to firms competing in cosmetic industry. Religiosity is one of the main factors that should be taken into account in promoting their cosmetic products.